ACCUMULATION OF THE NEW FORMS OF CAPITAL AMID GLOBAL ECONOMIC INSTABILITY - DUCHYNSKA, NINA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Accumulation of the modern forms of capital, namely intellectual, human, social and cultural have been described in the article. Tangible and intangible forms of capital accumulation, manifestation of extensive and intensive ways of capital accumulation have been figured out. Problems have been identified and the main trends of modern forms of capital development have been determined. New digital economy`s impact on changes in capital essence and the ways of its accumulation have been noted. It has been emphasized that there is a need for government regulation of these modern forms of capital interaction to support social development and stability and rise the national wealth.